Legal Certainty Regarding The Implementation Of The Regulation Of The Indonesian National Police Number 8 Of 2021 Concerning The Handling Of Criminal Acts Based On Restorative Justice In Settlement - Sri Sulistyawati; Iwan Setyawan; Mangaraja Manurung (Faculty of Law, Universitas Pekalongan, 2025)
This research aims to analyze the implementation of the restorative justice concept within the law enforcement system by the Indonesian National Police as regulated in Law Number 2 of 2002, the Chief of Police Circular Letter No. SE/8/VII/2018, and Police Regulation No. 8 of 2021. Restorative justice is a criminal case resolution approach that emphasizes restoring the condition of victims, offenders, and the community without undergoing formal judicial processes. However, in practice, inconsistencies often occur, particularly in petty theft cases, where some are resolved through restorative justice while others are processed through formal legal proceedings. This research adopts a normative juridical method supported by an empirical juridical approach and has both prescriptive and descriptive-analytical characteristics. Obstacles identified in the implementation include investigators' lack of understanding of restorative justice, a legalistic work culture among investigators, and limited public acceptance of out-of-court case resolutions. Additionally, Police Regulation No. 8 of 2021 does not specify the threshold of financial loss or consider the offender's motive, leading to varying interpretations. Therefore, regulatory reform, enhanced investigator capacity, and legal education for the public are necessary to ensure a more just and consistent application of restorative justice.